Reading Workshop & Formative Assessment: Maximizing Quality Reading Instruction - (:unkn) unknown (My University, 2017)
The purpose of this study was to closely examine an elementary teacher’s classroom practices in implementing reading workshop, to examine her assessment practices within this model and to see if, when, and how her assessment practices support or enhance constructivist practices within reading workshop. This qualitative case-study, was designed to examine, in depth, the teaching practices of one teacher attempting to implement constructivist teaching and learning practices in literacy instruction (reading in particular) in her classroom. The findings revealed that teachers implementing reading, when coupling that with formative assessment practices, can use those practices to enhance and grow students’ reading development by using a variety of supports in order to build strong reading practices. The data also highlights reading workshop as a constructivist model: where students were engaged in authentic literacy tasks that supported their reading development, where there was continual constructivist assessment practices tied to the learning students were doing, and where the teacher’s use of assessment practices was critical to increasing student’s awareness of their learning, to their independence and to their reading growth.
Keywords: Assessment; Formative; Reading; Workshop